PEMBERDAYAAN ANAK YATIM DAN IBU RUMAH TANGGA AISYIYAH MELALUI PROGRAM PELATIHAN BERCOCOK TANAM DAN PENGOLAHAN PRODUK MAKANAN BERBASIS SINGKONG - Nurul Huda; Aan Sofyan; Ngatono Ngatono (WARTA LPM, 2018)
Partners in the implementation of this community empowerment program is an orphan cared by Yayasan Panti Asuhan Keluarga Muhammadiyah (PAKYM) and homemakers who are members of the organisation Aisyiyah branch Laweyan Surakarta. Community empowerment program that has been done is to provide training cultivation of cassava plants and training of cassava-based food making. Training given to orphans in the form of cultivation practice of superior cassava crop. Training begins with the selection of cassava seeds, land preparation, and planting of cassava seeds. While the training provided to the members of Aisyiyah members is in the form of food processing training based on cassava. The purpose of this program is to provide entrepreneurial supplies for orphans with the hope of having an entrepreneurial spirit. Similarly, the practice of food processing based on cassava aims to provide skills for the Aisyiyah members in the desire to pioneer side business that can help increase family income.